Temperature difference between jugular bulb and pulmonary artery is associated with neurological outcome in patients with severe traumatic brain injury: A post hoc analysis of a brain hypothermia study. - Motoki Fujita; Yasutaka Oda; Kotaro Kaneda; Tadashi Kaneko; Eiichi Suehiro; Kenji Dohi; Yasuhiro Kuroda; Hitoshi Kobata; Ryosuke Tsuruta; Tsuyoshi Maekawa (PLoS ONE, 2023)
Background The purpose of this study was to examine whether the temperature difference between the jugular bulb and pulmonary artery (ΔTjb-pa) is associated with the neurological outcome of patients with severe traumatic brain injury (TBI). Methods We conducted a post hoc analysis of a multicenter randomized controlled trial of mild therapeutic hypothermia (TH, 32.0-34.0°C) or fever control (FC, 35.5-37.0°C) for the patients with severe TBI. ΔTjb-pa averaged every 12 h and the variation in ΔTjb-pa were compared between patients with favorable (n = 39) and unfavorable (n = 37) neurological outcomes. These values were also compared in the TH and FC subgroups. Results The average ΔTjb-pa values in patients with favorable and unfavorable outcomes were 0.24 ± 0.23 and 0.06 ± 0.36°C, respectively (P < 0.001). ΔTjb-pa trended significantly higher in the favorable outcome patients than in the unfavorable outcome patients throughout the 120 h after onset of severe TBI (P < 0.001). The variation in ΔTjb-pa from 0 to 72 h was significantly lower in the favorable outcome patients than in the unfavorable outcome patients (0.8 ± 0.8 vs 1.8 ± 2.5°C, respectively, P = 0.013). From 72 to 120 h, there was no significant difference in the variation in ΔTjb-pa. Significant differences between patients with favorable and unfavorable outcomes in ΔTjb-pa and the variation in ΔTjb-pa were similar in the TH subgroup, but not evident in the FC subgroup. Conclusions A reduction in ΔTjb-pa and greater variation in ΔTjb-pa were associated with an unfavorable outcome in patients with severe TBI, especially those treated with TH. When treating severe TBI patients, it is important to understand that there will be differences in temperature reflecting the brain environment and the systemic temperature, depending on the severity and outcome of TBI during TH.